Efektifitas Penusukan Titik Zusanli (ST 36) Dan Taichong (LR 3) Pada Kasus Melasma Ibu Guru SMPN III Colomadu, Karanganyar - Joko Tri Haryanto; Abhiseka Kristiyana (Poltekkes Kemenkes Surakarta, 2017)
Abstract: Transfixion Point Zusanli (St 36) and Taichong (Lr 3), Melasma. The effectiveness of Transfixion Point Zusanli (St 36) and Taichong (Lr 3) in the case of Junior High School Teacher Motherland of Melasma III Colomadu, Karanganyar. Melasma is a skin hyperpigmentation disorders face in the form of macula/patch symmetrical hyperpigmentation in the region of the forehead, around the nose, around the mouth, around the eyes, cheeks, and Chin with yellow-brownish or dark brownish to blackish, without subjective complaints of patients. Factors of the incidence of this disorder are ultraviolet radiation, hormone MSH, sex hormone imbalance and the contraceptive pill. Stabbing point Zusanli (ST 36) and Thaichong (Lr 3) can be per peran in the body's hormonal balance. The purpose of this study to the effectiveness of Zusanli and Taichong point stabbing on the case of melasma. the design research of using